2013
DOI: 10.1177/2156587213482942
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin-Rich Purple Corn Extract and Its Effects on the Blood Pressure of Adults

Abstract: This small-scale pilot study studied the potential benefit of taking a concentrated dose of anthocyanin 300 mg once a day for 3 weeks (purple corn extract) on blood pressure among untreated Peruvian adults with mild-to-moderate hypertension. A double-blind placebo-controlled randomized crossover trial using intention-to-treat analysis was conducted on 30 healthy men and women who received care at the Dos de Mayo Hospital (Lima, Peru) between September 2010 and August 2011. The 4-phase study compared blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 14 publications
0
5
0
8
Order By: Relevance
“…Several in vitro and in vivo studies with purple corn have reported anthocyanin‐linked functional properties such as antioxidant, anti‐inflammatory, anti‐carcinogenic, and anti‐hyperglycemic activity (Hagiwara and others ; Tsuda and others ; Ranilla and others ; Li and others ; Ramos‐Escudero and others ; Long and others ). Furthermore, a previous study also reported a reduced risk of hypertension among Peruvian adults due to the daily consumption of anthocyanin‐rich purple corn extract for a 3‐wk period (Finkel and others ).…”
Section: Introductionmentioning
confidence: 86%
“…Several in vitro and in vivo studies with purple corn have reported anthocyanin‐linked functional properties such as antioxidant, anti‐inflammatory, anti‐carcinogenic, and anti‐hyperglycemic activity (Hagiwara and others ; Tsuda and others ; Ranilla and others ; Li and others ; Ramos‐Escudero and others ; Long and others ). Furthermore, a previous study also reported a reduced risk of hypertension among Peruvian adults due to the daily consumption of anthocyanin‐rich purple corn extract for a 3‐wk period (Finkel and others ).…”
Section: Introductionmentioning
confidence: 86%
“…Recent in vitro and in vivo studies have reported the antioxidant, anti-hyperglycemic, anti-obesity, anti-inflammatory, and anti-cancer potential of purple corn extracts [4,[11][12][13][14]. The antihypertensive effect of purple corn has also been demonstrated in a clinical study [15].…”
Section: Introductionmentioning
confidence: 98%
“…Purple corn is known as a good source of natural antioxidants (Pascual-Teresa et al, 2002) and its benefic effects on health are under active study (Finkel et al, 2013;Hosoda et al, 2012;Huang et al, 2015). It can also be considered as an interesting natural alternative for mitigating the oxidation of essential fatty acids during extrusion (Camire et al, 2007).…”
Section: Introductionmentioning
confidence: 99%